Green certificates with Chinese characteristics: Will green certificates help China's clean energy transition? - Anders Hove; Gary Sipeng Xie (The Oxford Institute for Energy Studies, 2023)
Green power trading is a market-oriented way to promote a clean energy transition in China. In practice, China's leading instrument for this policy, the green certificate, has faced serious obstacles. A new OIES paper by Anders Hove and Gary Sipeng Xie examines the goals and history of the green certificate policy, and the major new challenges green certificates now face, as the market for renewables in China and abroad moves beyond the initial scale-up phase. In the past, China's green certificate market was hampered by a basic design flaw, in that projects selling green certificates would lose the right to collect feed-in tariff subsidies. This not only made project owners reluctant to sell certificates for less than the subsidies, but it also stifled market interest given the significant price premium this implied. Now that more projects are coming online without feed-in tariff subsidies, and given the government's belated recognition that green certificates would never take off unless removed from the issue of subsidy payments to older projects, this design problem looks set to fade into the background. But while there are positive trends in trading volumes and pricing, China's green certificate market faces significant near-term obstacles around transparency, regulation, and its role-whether in meeting the low-carbon goal of private companies or in contributing to the provincial targets and quotas on energy consumption and renewable integration.
Keywords: 330; China; Energy Transition; green certificate policy; green power trading